2011
DOI: 10.1093/imrn/rnr198
|View full text |Cite
|
Sign up to set email alerts
|

Tight Contact Structures on Laminar Free Hyperbolic Three-Manifolds

Abstract: ABSTRACT. Whether every hyperbolic 3-manifold admits a tight contact structure or not is an open question. Many hyperbolic 3-manifolds contain taut foliations and taut foliations can be perturbed to tight contact structures. The first examples of hyperbolic 3-manifolds without taut foliations were constructed by Roberts, Shareshian, and Stein [25], and infinitely many of them do not even admit essential laminations as shown by Fenley

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Other examples of tight contact structures on manifolds that admit no Reebless foliations were given by Etgü [8] in the case that the manifold is not Seifert fibered but hyperbolic. However, these examples are neither known to be universally tight, nor is it shown that there are tight contact structures for both orientations.…”
Section: Introductionmentioning
confidence: 99%
“…Other examples of tight contact structures on manifolds that admit no Reebless foliations were given by Etgü [8] in the case that the manifold is not Seifert fibered but hyperbolic. However, these examples are neither known to be universally tight, nor is it shown that there are tight contact structures for both orientations.…”
Section: Introductionmentioning
confidence: 99%